Allogeneic Stem Cell Transplantation Platforms With Ex Vivo and In Vivo Immune Manipulations: Count and Adjust. Issue 6 (1st June 2021) - de Witte, Moniek; Daenen, Laura G. M.; van der Wagen, Lotte; van Rhenen, Anna; Raymakers, Reiner; Westinga, Kasper; Kuball, Jürgen
Abstract : Various allogeneic (allo) stem cell transplantation platforms have been developed over the last 2 decades. In this review we focus on the impact of in vivo and ex vivo graft manipulation on immune reconstitution and clinical outcome. Strategies include anti-thymocyte globulin- and post-transplantation cyclophosphamide-based regimens, as well as graft engineering, such as CD34 selection and CD19/αβT cell depletion. Differences in duration of immune suppression, reconstituting immune repertoires, and associated graft-versus-leukemia effects and toxicities mediated through viral reactivations are highlighted. In addition, we discuss the impact of different reconstituting repertoires on donor lymphocyte infusions and post allo pharmacological interventions to enhance tumor control. We advocate for precisely counting all graft ingredients and therapeutic drug monitoring during conditioning in the peripheral blood, and for adjusting dosing accordingly on an individual basis. In addition, we propose novel trial designs to better assess the impact of variations in transplantation platforms in order to better learn from our diversity of "counts" and potential "adjustments." This will, in the future, allow daily clinical practice, strategic choices, and future trial designs to be based on data guided decisions, rather than relying on dogma and habits.